Impact of Pharmacist-Led Health Initiatives in Rural Alabama - Pilar Z. Murphy (The University of Alabama, 2023)
Perry County is a predominantly African American community in rural Alabama. The prevalence of cardiovascular risk factors such as obesity, diabetes, and hypertension is higher than average in the Perry County population. The Cardiovascular Risk Reduction Clinic, a collaboration between Samford University McWhorter School of Pharmacy, Sowing Seeds of Hope, and the Perry County Health Department, partnered with the Perry County Department of Transportation (DOT) to offer DOT employees, mostly African American men, health screenings and education delivered at times and locations convenient to their work schedules. The objective of the present study was to evaluate the impact of a community partnership with pharmacist-led health interventions on modifiable cardiovascular risk factors in participants lacking access to other community health initiatives due to work obligations. This study was a retrospective chart review evaluating changes in blood pressure and body mass index (BMI). Participants included DOT employees 18 years of age and older who participated in at least two health screenings 12 weeks apart. Over the course of the intervention, the average systolic blood pressure decreased by 6 mmHg, and the average diastolic blood pressure decreased by 4 mmHg. The baseline BMI average of 35.1 kg/m2 had dropped to 34.5 kg/m2 at 12 weeks. Although modest, the reductions in blood pressure and BMI indicate a potential for cardiovascular disease risk reduction. Lessons learned from this pilot project can inform the initiation of similar programs intended to decrease cardiovascular risk. Pharmacist-led interventions combined with community support can lead to positive cardiovascular results among rural communities.